The courts of pre-colonial South India : material culture and kingship - Howes, Jennifer (Royal Asiatic Society books., 2003)
An investigation of how the material culture of South Indian courts was perceived by those who lived there in the pre-colonial period. Howes peels away the standard categories used to study Indian palace space.